Optimal Distribution of Wind Turbines in Large Wind Farms Using Genetic algorithm (Journal of Hama University, 2021)
This research aims to obtain  an optimal distribution of wind turbines in large wind farms, in the planning stage, to extract the maximum output power from the wind farms by reducing the wake effect losses between the wind turbines. So that, a genetic algorithm (GA) has been used in this paper for optimizing wind turbines distribution within a hypothetical wind farm considering three different cases of wind, i.e. constant wind speed with fixed wind direction, constant wind speed with variable wind direction, variable wind speed with variable wind direction.In this paper, Jensen's Model has been used to represent the wake effects between the wind turbines, which through it we can determine the wind speed in front of all wind turbines affected by the wake, and then calculate the total produced power from the wind farm annually.The code for the algorithm of the optimal distribution of wind turbines within large wind farms has been written in MATLAB environment. The code has been tested on a hypothetical wind farm, then the obtained results (the precise coordinates of wind turbines, which achieved the maximum output power of the wind farm at three wind cases) are compared with the results of the previous works. The results we have obtained have shown a remarkable superiority over those introduced in the previous works.